Insights Into a Watermelon Virome Contribute to Monitoring Distribution of Whitefly-Borne Viruses - Neta Luria; Elisheva Smith; Noa Sela; Amnon Koren; Oded Lachman; Aviv Dombrovsky (Phytobiomes Journal, 2019)
The composition of a plant virome may represent spatiotemporal patterns of plant virus abundance. Using next generation sequencing, we investigated the viromes of watermelon fruits grown in two adjacent open fields located in Eastern Israel: Kalia and Mitzpe-Shalem. The two viromes were comprised of distinct virus species and genera. Studying spatial and temporal effects on virus occurrence, we detected the crinivirus Cucurbit yellow stunting disorder virus in Kalia and not in Mitzpe-Shalem, irrespective of collection time. A spatial effect was also observed regarding the occurrence of the begomovirus Watermelon chlorotic stunt virus, which was not detected in watermelons from Kalia, but rather in watermelon fruit in Northern Israel in 2018. A temporal effect was observed on the appearance of the ipomovirus Cucumber vein yellowing virus, which was detected in watermelons from Kalia in 2017 and was absent in the 2016 virome analysis. Importantly, regardless of temporal and spatial effects, the crinivirus Cucurbit chlorotic yellows virus, which was new to Israeli landscape, was detected in all the tested watermelon plants. These changes in viral abundance were associated with an early whitefly (Bemisia tabaci) occurrence, which might be the cause for the severe disease spread in watermelons.